Experimental Study of Thermophysical Properties of TiO2 Nanofluid - Abdulwahab, Majid I.; Thahab, S.M.; Dhiaa, Asmaa H. (Iraqi Journal of Chemical and Petroleum Engineering, 2016)
Titanium-dioxide (TiO2) nanoparticles suspended in water, and ethanol based fluids have been prepared using one step method and characterized by scanning electron microscopy (SEM), and UV–visible spectrophotometer. The TiO2 nanoparticles were added to base fluids with different volume concentrations from 0.1% to1.5% by dispersing the synthesized nanoparticles in deionized water and ethanol solutions. The effective thermal conductivity, viscosity and pH of prepared nanofluids at different temperatures from 15 to 30 oC were carried out and investigated. It was observed that the thermal conductivity, pH, and viscosity of nanofluids increases with the increase in TiO2 nanoparticle volume fraction.  The thermal conductivity of TiO2 nanofluids significantly increases linearly with increasing particle vol. fraction at different temperature values and also it was found that the viscosity increases with increasing particle vol. fraction and decreases with the increase in temperature.